Strategi Kepala Sekolah dalam Meningkatkan Motivasi Kerja Guru melalui Kebijakan Promosi dan Penghargaan di KB-TK Islam Al Azhar 28 Solo Baru - Salsabila Qurratu’ain ‘Abidah (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
Teacher motivation is a key factor influencing the quality of learning. The principal plays a strategic role in enhancing teacher motivation through effective promotion and reward policies. This study aims to describe the principal’s strategies in improving teacher motivation using a qualitative case study approach at an Islamic early childhood institution in Sukoharjo. Data were collected through interviews, observation, and documentation, and analyzed through data reduction, display, and conclusion drawing. The results show that the principal improves teacher motivation through a transparent promotion system, non-material rewards, and a supportive work environment. These strategies enhance teachers’ enthusiasm, loyalty, and responsibility. Thus, well-managed promotion and reward policies effectively strengthen teacher motivation and improve educational quality.